Exploring the Educational Landscape: The Impact of Post-Covid Online Learning on Physics Education Undergraduates' Academic Engagement and Achievement - Seni Susanti; Riki Purnama Putra; Rena Denya Agustina; Nguyen Phu Quy; Hariman Surya Siregar; Jose da Silva (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
Covid-19 is a pandemic that can change the culture of the learning process, which Covid-19 pandemic brought transformation and new habits, and these new habits had to be adjusted based on the rules and regulations that apply in the country. Globally, Covid-19 made educators have to quickly adapt to new teaching methods, and students faced difficulties with internet access, digital literacy, and maintaining motivation in a remote environment. However, around 2021, in quartile 3 to be precise, in Indonesia changes have occurred again to adapt to new habits, namely the post-Covid-19 recovery period, where the education system has again transformed from online learning habits to offline learning. This study aims to find out how interest in studying and learning outcomes affect undergraduate students of physics education in the post-COVID-19 era. The research method is carried out quantitatively, which consists of filling out a questionnaire for interest in studying which consists of five aspects; (1) Exploration; (2) Curiosity; (3) Boredom; (4) Attention; and (5) Enjoyment. This study used two groups namely pre covid-19 and post covid-19 with a total of 67 samples used, then processing of learning outcomes data prerequisite tests such as normality and homogeneity tests were carried out then hypothesis testing using independent sample t-test and Cohen's D Effect Size to know the how big the difference between two groups, then a deep interview is conducted to know deeply. This research found results in which undergraduate physics education students in the post-COVID-19 era experienced low interest in studying and learning outcomes due to the shock culture and the influence of student organizations which they thought were more interesting than academic activities.